Interframe bus encoding technique and architecture for MPEG-4 AVC/H.264 video compression - Asral, Bahari Jambek; Arslan, Tughrul; Erdogan, Ahmed T. (IEEE, 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/